Systematic Literature Review Faktor-Faktor yang Mempengaruhi Produksi Usahatani Kelapa Sawit di Pulau Sumatera Indonesia - Wardah Helga Prasetyani; Sarwedi Sarwedi (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
This study analyzes the factors influencing oil palm plantation production on the Island of Sumatra, a major commodity in the plantation sector that plays a significant role in regional economic growth. The effective use of production factors and proper management can lead to increased oil palm plantation production. This study applies a Systematic Literature Review (SLR) approach. The research aims to: 1) determine the respondent selection method, 2) determine the data collection techniques, 3) identify production factor variables, and 4) analyze the factors influencing production. The results show that the most commonly used respondent selection methods are Proportionate Stratified Sampling and Slovin, with the primary data collection techniques using questionnaires and interviews from 200 respondents. Overall, 26 production factors were considered. The production factors that have significant impacts in oil palm farming are land area, labor, and plant age, as identified in 6 out of the 12 analyzed articles (50%). The implications of this research provide insights for farmers and stakeholders to optimize the use of production factors, which is expected to increase productivity and sustainability of oil palm plantations and contribute to the economy of the Island of Sumatra.